Association between land use change and exposure to zoonotic pathogens–Evidence from selected case studies in Africa - Bett, Bernard K.; Ngwili, Nicholas; Nthiwa, Daniel; Alonso, Silvia (Elsevier, 2019)
The demand for food and other ecosystem services have risen in the recent past in many parts of the world due to increasing human population. This has promoted agricultural intensification and increased extraction of natural resources particularly in the sub-Saharan Africa where people derive livelihoods from their local environments. These developments invariably influence transmission patterns (positively or negatively) for a wide range of infectious diseases. In this paper, three case studies from East and southern Africa are used to demonstrate linkages between land use change and risk of exposure to zoonotic diseases. They identify two common processes that influence disease risk including (i) modification of vector, pathogen and host niches, and (ii) changes in reservoir host population distribution. Potential ways of managing disease risks in each case are also discussed.